The Influence of Job Stress on Employee Deviant Behavior in the Workplace - Suradiwirja, Heimemayu Rudiyono (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to determine the effect of job stress on deviant behavior in the workplace. Job stress is a condition of tension experienced by individuals due to work pressures that exceed their ability to cope. Deviant behavior in the workplace is an action taken by employees who violate organizational norms and rules, such as stealing, arriving late, or leaving work early. Data was collected through “library research” by comparing several relevant scientific journals. The results showed that job stress has a positive and significant effect on deviant behavior in the workplace. This means that the higher the level of work stress experienced by employees, the higher their tendency to engage in deviant behavior. This research provides implications for companies to pay attention to the factors that cause work stress and implement effective stress management strategies to minimize deviant behavior in the workplace.